Insights into the phylogeny of Northern Hemisphere Armillaria: Neighbor-net and Bayesian analyses of translation elongation factor 1-α gene sequences. (2nd January 2017) - Klopfenstein, Ned B.; Stewart, Jane E.; Ota, Yuko; Hanna, John W.; Richardson, Bryce A.; Ross-Davis, Amy L.; Elías-Román, Rubén D.; Korhonen, Kari; Keča, Nenad; Iturritxa, Eugenia; Alvarado-Rosales, Dionicio; Solheim, Halvor; et al.
ABSTRACT: Armillaria possesses several intriguing characteristics that have inspired wide interest in understanding phylogenetic relationships within and among species of this genus. Nuclear ribosomal DNA sequence–based analyses of Armillaria provide only limited information for phylogenetic studies among widely divergent taxa. More recent studies have shown that translation elongation factor 1-α ( tef1 ) sequences are highly informative for phylogenetic analysis of Armillaria species within diverse global regions. This study used Neighbor-net and coalescence-based Bayesian analyses to examine phylogenetic relationships of newly determined and existing tef1 sequences derived from diverse Armillaria species from across the Northern Hemisphere, with Southern Hemisphere Armillaria species included for reference. Based on the Bayesian analysis of tef1 sequences, Armillaria species from the Northern Hemisphere are generally contained within the following four superclades, which are named according to the specific epithet of the most frequently cited species within the superclade: (i) Socialis/Tabescens (exannulate) superclade including Eurasian A. ectypa, North American A. socialis ( A. tabescens ), and Eurasian A. socialis ( A. tabescens ) clades; (ii) Mellea superclade including undescribed annulate North American Armillaria sp. (Mexico) and four separate clades of A. mellea (Europe and Iran, eastern Asia, and two groups from North America); (iii) Gallica superclade including Armillaria Nag E (Japan), multiple clades of A. gallica (Asia and Europe), A. calvescens (eastern North America), A. cepistipes (North America), A. altimontana (western USA), A. nabsnona (North America and Japan), and at least two A. gallica clades (North America); and (iv) Solidipes/Ostoyae superclade including two A. solidipes / ostoyae clades (North America), A. gemina (eastern USA), A. solidipes / ostoyae (Eurasia), A. cepistipes (Europe and Japan), A. sinapina (North America and Japan), and A. borealis (Eurasia) clade 2. Of note is that A. borealis (Eurasia) clade 1 appears basal to the Solidipes/Ostoyae and Gallica superclades. The Neighbor-net analysis showed similar phylogenetic relationships. This study further demonstrates the utility of tef1 for global phylogenetic studies of Armillaria species and provides critical insights into multiple taxonomic issues that warrant further study.